Effects of gas blowing condition on formation of mixed halide perovskite layer on organic scaffolds. Issue 14 (13th July 2017) - Gotanda, Takeshi; Mori, Shigehiko; Oooka, Haruhi; Jung, Hyangmi; Nakao, Hideyuki; Todori, Kenji; Nakai, Yutaka
Abstract: Abstract : Perovskite solar cells are promising for realizing high power conversion efficiency (PCE) with low manufacturing costs, but efficient coating methods are needed for commercialization. Here, a gas blowing method was used to fabricate perovskite solar cells and was found to create a smooth perovskite layer and to prevent voids in large-area cells, when organic materials were used as scaffolds for forming the perovskite. A PCE of 13% in a 1 cm 2 active area is achieved by tuning the band-gap energy of MAPbX3 via substitution of Br for I ions in X sites. Incorporation of a poly(3, 4-ethylenedioxythiophene) hole transport layer with a higher work function increased the open circuit voltage of the solar cells. All layers of the cells were fabricated at low temperatures (<140 °C), which makes it possible to incorporate a polymer substrate for producing flexible solar cells and high-throughput fabrication.